Aging and Language: Maintenance of Morphological Representations in Older Adults - Royle, Phaedra; Steinhauer, Karsten; Dessureault, Émie; Herbay, Alexandre C.; Brambati, Simona M. (Frontiers in Communication, 2019)
Studies employing primed lexical decision tasks have revealed morphological facilitation effects in children and young adults. It is unknown if this effect is preserved or diminished in older adults. In fact, only few studies have investigated age-related changes in morphological processing and results are inconsistent across studies. To address this issue, we investigated morphological inflection compared to orthographic and semantic activation in young and older adults. Twenty-six adults aged 60–85 and 22 younger adults aged 19–28 participated. We probed verb recognition using a sandwich-masked primed lexical decision paradigm. We investigated perceptibility effects using different prime presentation times (33, 66 and 150 ms), and prime types with priming conditions involving orthographic (e.g., cassis – CASSE ‘blackcurrant – break’), regular inflection morphological (cassait – CASSE ‘broke – break’), and semantic primes (brise – CASSE ‘break – break’) and their controls, while measuring response accuracy and reactions times. Response accuracy analyses revealed that older participants performed at ceiling on the lexical decision task, and that accuracy level was higher compared to young adults. Reaction times data revealed effects of group (young vs. older adults), priming condition and an interaction of age group and morphological priming, but no prime presentation time effects. Both young and older adults presented a significant facilitation effect (reduced reaction times) in the orthographic and morphological priming conditions. No semantic effects were observed in either group. Younger adults also showed a significantly stronger morphological priming effect, while older adults showed no difference between orthographic and morphological priming when comparing priming magnitudes. These findings suggest (1) that regular inflectional morphological processing benefits lexical access in younger French adults, confirming studies in other languages, and (2) that this advantage is reduced at older ages.